Settler Colonialism and the Logic of Double Elimination†. Issue 4 (19th May 2019) - Svirsky, Marcelo; Ben-Arie, Ronnen
Abstract : According to the logic of elimination that subtends settler colonial projects, native populations are displaced in order to replace their systems of life, a process that structures invasion in its initial stages as in the present. By looking into the case of modern Palestine in an integrative fashion, in this essay we suggest that settler colonialism targets native populations along with social formations – established ways of life – that nurture native life in various ways. We define this settler specificity as the "logic of double elimination." Our story shows that in Palestine, Zionism developed and the Israeli state was eventually established by means of (a) the continuing elimination of the Arab-Palestinians and their sovereignty, and (b) the destruction of the social infrastructure and identities that fostered Arab–Jewish shared life and forms of cooperation as they flourished in Ottoman times, and the prevention of these forms as they survived into the British Mandate era. These operations of erasure cannot be understood, as Patrick Wolfe persuasively suggested, but as mediated by race. By expanding the conceptualization of the settler logic of elimination we aim at contributing to a broader understanding of the settler colonial phenomena and of decolonization.